(untitled) (Revista Ciência Agronômica, 2021)
Brazil stands out in the renewable energy sector due to the growing demand for clean energy sources, mainly with biodiesel production, which uses vegetable oils and animal fats as raw material. With this, research has been developed with oilseed plants for this purpose and, among these plants, Jatropha has stood out for its productivity and ability to grow in regions with water scarcity. Thus, it is necessary to study the growth of this plant over time to assist management techniques and detection of factors that affect the plant development. Therefore, modeling this type of growth can subsidize knowledge and application of effi cient techniques for agricultural practices. The objective of this study was to fi t and compare the nonlinear Logistic and Gompertz models with four parameters in the description of growth in height of the Jatropha plant according to days after the phenological cycle in the second year of the plant development, totaling 25 observations. The models were fi t using the statistical software R, considering the fi rst order autoregressive error structure for the CNPAE-169 and CNPAE-259 accessions. All models fi t well to the data from the three accessions under study, but the Logistic model stood out for the CNPAE-169 and CNPAE-102 accessions and the Gompertz model for the CNPAE-259 accession. The CNPAE-102 accession stood out from the others, presenting greater height in the study period.